The Saqmolo' Project: Protocol for a Randomized Controlled Trial Examining the Impact of Daily Complementary Feeding of Eggs on Infant Development and Growth in Guatemala. (7th June 2021) - Montenegro-Bethancourt, Gabriela; Wallace, Taylor; Rohloff, Peter; Jimenez, Elizabeth Yakes; Proaño, Gabriela; McCabe, George; Steiber, Alison
Abstract: Objectives: Studies in Ecuador and Malawi have demonstrated mixed effects of interventions involving daily complementary feeding of eggs on child growth. For example, in Malawi, the egg intervention had no overall effect on child development. There is a need to test the effects of egg interventions on child growth and development in other settings with high prevalence of stunting and in the context of other nutritional interventions. The Saqmolo' (i.e., "egg" in the Mayan language, Kaqchiquel) study aims to evaluate the impact of adding 1 egg per day to local standard nutrition care (LSNC) on child development, in rural Maya infants from Guatemala. Methods: In a community-based, individually randomized, controlled comparative effectiveness trial among rural indigenous Maya children ( n = 1200), starting at 6–9 months at baseline, we will compare the impact of adding one egg per day to LSNC with LSNC alone. LSNC includes: growth monitoring, medical care, deworming medication, multiple micronutrient powders for point of use food fortification, and individualized complementary and responsive feeding education for caregivers. Intervention and control groups will be visited once per month during 6-months and adherence will be monitored during the visits and through phone calls for the first 2 months in both groups at the same frequency. The primary outcome is differences in child global development (measured by Caregiver Reported Child Development Instruments –CREDI-and the Guide for Monitoring Child Development GMCD); secondary outcomes include: growth (z-scores for weight for age, length for age, weight for length, and head circumference for age), and diet quality (using the World Health Organization's infant and young child feeding indicators). Results: N/A (submitting study protocol abstract). Conclusions: This study will provide new evidence on the potential effect of increased egg accessibility in high prevalence stunting areas along with integrated nutrition care on child development. The results may help to inform public health decision-making regarding resource allocation for effective nutrition interventions during the complementary feeding period in Guatemala. Funding Sources: This work was supported by the Academy of Nutrition and Dietetics Foundation via an investigator-initiated research grant from the Egg Nutrition Center.